SMAD4 Y353C promotes the progression of PDAC - Wang, Zusen; Li, Yongxing; Zhan, Shixiong; Zhang, Lu; Zhang, Shun; Tang, Qian; Li, Miaomiao; Tan, Zhen; Liu, Shiguo; Xing, Xiaoming (BMC cancer, 2019)
SMAD4 is frequently inactivated and associated with a poor prognosis in pancreatic ductal adenocarcinoma (PDAC). Abnormal SMAD4 expression also plays an important role in the malignant progression of PDAC. We investigated SMAD4 status in PDAC by immunohistochemical methods to explore the relationships between SMAD4 expression and clinicopathological features and then detected SMAD4 mutations by Sanger sequencing in 95 patients with PDAC to identify new mutation sites in PDAC. We further evaluated the effects of a missense mutation, Y353C, in the SMAD4 MH2 domain, on cell proliferation and migration in vitro. Immunohistochemistry showed that the expression of SMAD4 in PDAC carcinoma tissue was significantly lower than that in normal pancreatic tissue, and negative SMAD4 expression was closely related to tumour diameter, staging, lymph node metastasis and differentiation. Sanger sequencing analysis showed that the rate of SMAD4 mutation was 11.8% in 85 PDAC cases, and the novel SMAD4 Y353C missense mutation identified in this study promoted cell migration and invasion without affecting cell proliferation in vitro. Furthermore, SMAD4 Y353C resulted in reduced expression of E-cadherin and increased expression of Vimentin compared with wild-type SMAD4 overexpression. This study supports the key role of SMAD4 as a tumour suppressor gene in PDAC and shows that SMAD4 Y353C is associated with poor progression of PDAC.